The Tetradic Heart of Darkness: Comparing three dark-side instruments. (September 2021) - Furnham, Adrian; Horne, George
Abstract: In this two-study paper we examined three dark-side measures: the short Dark Tetrad measuring four dark-side traits; the SCATI measuring 14 personality disorders (PDs) and the SAPAS a single item measure for each disorder. The first study ( N  = 502) looked specifically at the new Dark Tetrad. Over 500 British Adults completed it and a confirmatory factor analysis confirmed the Tetrad factor structure. There were large sex differences in half of the items. We also examined demographic, ideological and self-rated correlates which showed ratings of political beliefs and self-rated attractiveness associated with different traits. The second study ( N  = 273) looked at the correlations between the three measures and the overlap between self-report tests of the same trait. All four of the Tetrad traits correlated with over half of the PDs. We found the highest correlation between the two scores of Narcissism, but that the single measure most associated with Borderline, Depressive and Dependent PD. The discussion considers the use of different clinical and sub-clinical instruments which measure the same variables. Highlights: A confirmatory factor analysis confirmed the Dark Tetrad factor structure in study 1 There were large sex differences in half of the items. The second study looked at Tetrad factors and 14 Personality Disorders All four of the Tetrad traits correlated with over half of the Personality Disorders Highest correlations between the Dark Tehrad factors and Narcissism, Borderline, Depressive and Dependent PD.